(untitled) - Jotisalikorn, Chami (Singapore, 2005)
Contemporary Asian Bedrooms opens the door to a new world of slumber retreats, showcasing some of the most eye-catching new bedroom designs in luxury homes and hotels in Southeast Asia. Shown here are a range of new design trends, from Zen minimalist to exuberant color kaleidoscopes, that make contemporary bedrooms more than just a spot for sleeping. This book gives homeowners and designers a look at new ideas, shapes, colors and textures that transform the places we sleep into high-style, must-have dream spaces.
Keywords: Bedrooms,Interior decoration,Interior decoration; Asian influences; Asia,Asia